Implementasi Google Drive untuk Mendukung Pelayanan Administrasi dalam Jaringan pada Program Studi Teknik Informatika Universitas Surakarta - Djoko Sutanto; Lia Setiarum Adi Putranti (Jurnal Ilmu Komunikasi PROGRESSIO, 2022)
The task of the administrative staff is to provide services to lecturers and students, but the ratio of administrative staff to lecturers and students is not ideal, and the CoViD-19 pandemic demands changes to the service system in order to keep performing well. This study examines the use of Google Drive in assisting online administrative services for lecturers and students. The type of research used is descriptive qualitative, with data collection techniques from interviews, observations and documentation. The validity of the data with triangulation techniques, and interactive models were used for data analysis. This research shows that Google Drive is quite successful in supporting the implementation of online administration services. This is evidenced by the perceptions of lecturers and students who feel that they get the convenience of service, although there are still inhibiting factors. Administration staff should carry out regular monitoring to improve Google Drive implementation.